Up-Scaling and Optimisation of Fire Fighting Ground Vehicle Track System - Tan, CheeFai; Ranjit Singh, Sarban Singh; V.K. , Kher; H.F. , Kong (Trans Tech Publications, Switzerland, 2013)
Current UTeM’s fire fighting machine is developed to operate indoor only. It is not efficient when it is operating on rocky surfaces (outdoor) as it faces the problem of shock and vibration reduction. The track system of the machine cannot move smoothly because the rollers are fixed to the chassis. This paper describes the method of up-scaling and optimising the track system for the current fire fighting machine. The new track system concept is firstly developed by using Computer-Aided Design (CAD) and Computer Aided Engineering (CAE) software. Subsequently a prototype is built to validate the functionality of the new track system which is more efficient in absorbing the vibration and shock. Analysis and optimisation of the prototype is performed using CAD method with the CATIA V5 R16 software.